The Relationship Between Procrastination, Self-Efficacy, and Self-Control in Relation to Anxiety Among Medical Students - Aflah, Imam Nabil; Adiwibawa, Danang Nur; Ronanarasafa; Mirah, I Gusti Ayu Agung; Chee Kok Yoon (Jurnal Psikiatri Surabaya, 2025)
Introduction: Anxiety is a condition characterized by apprehension and the persistent concern that something negative is about to occur, accompanied by physical, cognitive, and behavioral symptoms. There are two main factors influencing anxiety: internal and external factors. However, other contributing factors include procrastination, self-efficacy, and self-control. Methods: This study used an observational analytic design with a cross-sectional approach. A stratified random sampling technique was employed, yielding a sample size of 83 respondents. The data collected were analyzed using the chi-square correlation test. Results: The prevalence of high procrastination levels was observed in 37 respondents (44.6%). Low self-efficacy was reported in 49 respondents (59%), and low self-control in 41 respondents (49.4%). A total of 47 respondents (56.6%) experienced anxiety. There was a significant association between procrastination and anxiety, with a p-value of 0.000 (p < 0.05). Similarly, significant associations were found between self-efficacy and anxiety (p-value = 0.000, p < 0.05) and between self-control and anxiety (p-value = 0.000, p < 0.05). Conclusions: Significant associations were observed between procrastination, self-efficacy, and self-control with anxiety among students of the Faculty of Medicine at Universitas Islam Al-Azhar.